As famílias de crianças e adolescentes em contextos de violação de direitos - Souza, Gabriel Pereira de (2011)
The goal of this study was to analyze the families of children and adolescents at risk with history of violation of rights. The conceptions of authors based in the Critical Theory (Azevedo, 2009; Bruschini, 2009) were used as support, in order to understand the category family. To define risk, in relation to children and adolescents, the authors Lescher et al. (2004) and Hillesheim and Cruz (2008) were used as references; in relation to the family, Cecconello and Koller (2003), Cecconello (2003), Paludo (2008) and Paludo and Koller (2008) were used. The perspective of human rights of Bobbio (2004) was utilized to determine the violation of rights of children and adolescents, which has been positivized from legal frameworks. The applied methodology was qualitative, using semi-structured interviews, participant observation, home visits and field diaries as instruments as techniques. Seven families assisted by an institution on which operates a PETI Center in João Pessoa-PB, with 01 child and 01 adult per family. The existence of history of violation of rights was used as a criterion of child participation and, for the adults, the conditions to accompany the child at the Center and to identify themselves as responsible for it. Data analysis was conducted using the perspective of the discursive practices of Spink (2010), organizing the interviews on maps, from which the senses and the repertories utilized in the discursive practices of the participants were identified, using the field diary to support the analysis. Families participating in this study share a history marked by migration in search of new perspectives of life and survival strategies that represent, for poor families, the possibility to improve their lives, through the conception of a family. Families are conceived as members that share blood ties, of affect, or as those that live in the same household, being in several distinct formats. Risks were represented by the precarious living conditions, low familiar income, unemployment, violence at the community where they live, difficult of access to the public policies and also by the physical and psychological violence. The strategy of facing these risks goes for two ways: informal and precarious job, with female labor, and; the programs of incoming transference of the Federal Government. A variety of violation of rights that occurred in the context of the families was identified, not only by the families, but also by the State. The factors reported show the need for the adult to exercise the power over the child, when it does not behave adequately, also reproducing the history of domestic violence experienced by the adults when child or by the gender violence represented by the relationship with the husband. The rights are recognized by the participants and often referred to the PETI Center and the interventions and confrontations occur by a web of relations, institutional or not, including their own family that sometimes violates, sometimes defends. The discursive practices reveal the family, as conceived by the Critical Theory, by the diversity, by the complexity that incorporates contradictions in the struggle for survival, generating conflicts between generations and between gender, related to the power and the position that they occupy in the relationships; include diversities, that do not mean disruption, but forms of to organize themselves for living, face difficulties, where coexist solidarity and conflicts.